2021
DOI: 10.1186/s12864-021-07518-0
|View full text |Cite
|
Sign up to set email alerts
|

A genome-scale CRISPR interference guide library enables comprehensive phenotypic profiling in yeast

Abstract: Background CRISPR/Cas9-mediated transcriptional interference (CRISPRi) enables programmable gene knock-down, yielding loss-of-function phenotypes for nearly any gene. Effective, inducible CRISPRi has been demonstrated in budding yeast, and genome-scale guide libraries enable systematic, genome-wide genetic analysis. Results We present a comprehensive yeast CRISPRi library, based on empirical design rules, containing 10 distinct guides for most gene… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 49 publications
0
19
0
Order By: Relevance
“…Between 0.5-10 μ g of purified genomic DNA from each library sample was sheared into ∼350 nucleotide length fragments by sonication for 10 min on ice using a Diagenode Bioruptor. Sheared gDNA was then in vitro transcribed into RNA (denoted gRNA below and in analysis code) starting from the T7 promoter region in the insert cassette, similar to previous approaches ( 85, 86 ), using a HiScribe T7 High Yield RNA Synthesis Kit (NEB E2040S). Transcribed gRNA was treated with DNase I (NEB M0303S) and cleaned using an RNA Clean and Concentrator kit (Zymo R1013).…”
Section: Materials and Methods Plasmid Constructionmentioning
confidence: 99%
“…Between 0.5-10 μ g of purified genomic DNA from each library sample was sheared into ∼350 nucleotide length fragments by sonication for 10 min on ice using a Diagenode Bioruptor. Sheared gDNA was then in vitro transcribed into RNA (denoted gRNA below and in analysis code) starting from the T7 promoter region in the insert cassette, similar to previous approaches ( 85, 86 ), using a HiScribe T7 High Yield RNA Synthesis Kit (NEB E2040S). Transcribed gRNA was treated with DNase I (NEB M0303S) and cleaned using an RNA Clean and Concentrator kit (Zymo R1013).…”
Section: Materials and Methods Plasmid Constructionmentioning
confidence: 99%
“…McGlincy et al showed a comprehensive yeast CRISPRi library, based on empirical design rules, containing 10 distinct guides for most genes, which providing a strategy for genome-wide CRISPR interference screening in budding yeast [92]. Furthermore, a short communication introduced a GDi-CRISPR system (gene drive delta site integration system by the CRISPR system) for multi-copy integration in S. cerevisiae, which holds great promising for advancing the development of S. cerevisiae multi-copy integration tools [93].…”
Section: Synthetic Genomics and The Use Of Crispr Technology In Synthetic Genomics Of S Cerevisiaementioning
confidence: 99%
“…The arrival of CRISPR-Cas9 and related genome editing tools [394,395] is well enough known as not to need detailed review (and many are available, e.g. [369,[396][397][398][399][400][401][402][403][404][405][406][407][408][409][410]).…”
Section: Crispr-cas-based Genome Engineeringmentioning
confidence: 99%